Nesting ecology of sympatric species of wool carder bees (Hymenoptera: Megachilidae: Anthidium) in South America - Vitale, Nydia Luciana (2017)
Using a total of 14,043 trap-nests (potential nest for bees), we documented the nest architecture, host plants, seasonality,and associated organisms of the following six native species of Anthidium (Megachilidae: Anthidiini) from the CentralMonte Desert in Mendoza, Argentina: A. andinum Jo¨ rgensen; A. chubuti Cockerell; A. decaspilum Moure; A. friesei Cockerell;A. rubripes Friese; and A. vigintipunctatum Friese. Each species exhibited unique features in the arrangement of thefibers used to make their cells, and in the type of material used in the nest plug. Bees used a total of 41 plant species,but relied heavily on Prosopis flexuosa (Fabaceae) and Larrea spp. (Zygophyllaceae). Most bee species are univoltine andexhibited delayed emergence. The oil beetle Nemognatha sp. (Coleoptera: Meloidae) and the cuckoo wasp Chrysis striatulaBohart (Hymenoptera: Chrysididae) are recorded for the first time for Anthidium. Nemognatha sp. was the mostcommon brood parasite but C. striatula caused the highest brood mortality.